Epistemological Perspective of Mathematical Philosophy On Technology-Based Learning - Siregar, Nurhasanah; Dewi, Izwita; Ningsih, Faiz Ahya (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
This research is a literature study (library research) that uses a qualitative approach. The aim of this research is to examine the extent to which technology plays a role in mathematics learning from the perspective of the epistemology of mathematical philosophy. The study of the epistemology of the philosophy of mathematics that is being discussed is how does the development of the philosophy of mathematics influence technology? What is the relationship between the philosophy of mathematics and technology-based learning? As well as examples of technology-based mathematics learning models. The results and discussion of this article can be concluded: Philosophy is a science that has a close relationship in human life.The philosophy of mathematics influences the development of technology in general. Technological developments influence the development of learning. From a learning perspective, technology is not only something related to machines, but also related to people, ideas and activities in learning. The use of technology in the form of hardware and software can improve student learning outcomes. Currently, there are many software tools available for use in learning, such as GeoGebra. Choosing the right learning model and mathematics learning technology can make learning more effective